Pengaruh Kemampuan Gerak Motorik Kasar Terhadap Keberhasilan Belajar Lempar Tangkap Bola Siswa Tunagrahita Di SLB Negeri Wiradesa (Indonesian Journal for Physical Education and Sport, 2022)
This research is to determine the ability of gross motor movements to successfully learn to catch the ball of lightly impaired students Wiradesa State Out-of-state Schools. This research a one-group pretest posttest design. The sampling technique used was a total sampling .The instruments used in this study used a small ball capture mpar test with a wall target with a distance of one meter. The data analysis used by this study includes prerequisite tests, descriptive analysis and hypothesis tests. The results of this study are related to the results of the t test difference between the pretest group and the wall ball capture throw posttest showing a value of 0.000 < 0.05 which means that the training program has a significant influence on the ability to throw catch the ball. Meanwhile, the t test difference between the pretest group and the posttest throwing the ball back and forth wall showed a value of 0.000 < 0.05, meaning that the training program provided had a significant influence on the ability to catch the ball back and forth. Based on the results of the study, it can be concluded that basic motor movement training affects the success of throwing balls of students at Wiradesa State Out-of-state Schools, Pekalongan Regency, Pekalongan Regency. For teachers, it is hoped that the health assessment teacher can develop and provide an interesting learning method for students to be motivated in participating in teaching and learning activities. This research is to determine the ability of gross motor movements to successfully learn to catch the ball of lightly impaired students Wiradesa State Out-of-state Schools. This research a one-group pretest posttest design. The sampling technique used was a total sampling .The instruments used in this study used a small ball capture mpar test with a wall target with a distance of one meter. The data analysis used by this study includes prerequisite tests, descriptive analysis and hypothesis tests. The results of this study are related to the results of the t test difference between the pretest group and the wall ball capture throw posttest showing a value of 0.000 < 0.05 which means that the training program has a significant influence on the ability to throw catch the ball. Meanwhile, the t test difference between the pretest group and the posttest throwing the ball back and forth wall showed a value of 0.000 < 0.05, meaning that the training program provided had a significant influence on the ability to catch the ball back and forth. Based on the results of the study, it can be concluded that basic motor movement training affects the success of throwing balls of students at Wiradesa State Out-of-state Schools, Pekalongan Regency, Pekalongan Regency. For teachers, it is hoped that the health assessment teacher can develop and provide an interesting learning method for students to be motivated in participating in teaching and learning activities.